2013
DOI: 10.1021/op300292a
|View full text |Cite
|
Sign up to set email alerts
|

Applying QbD Principles To Develop a Generic UHPLC Method Which Facilitates Continual Improvement and Innovation Throughout the Product Lifecycle for a Commercial API

Abstract: The application of quality-by-design (QbD) principles for new chemical entities (NCEs) is highlighted in several publications. QbD, however, is rarely applied to marketed APIs. Lifecycles of existing APIs are extending. With this extension the focus on drug safety and compliance requires up-to-date knowledge of the product and its production process as over the years expectations in this respect have shifted. We applied QbD principles in order to set up an improved control strategy for the final five steps in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…A preliminary study showed that using more than 70% acetonitrile in the mobile phase eluted MF after 7 min at a pH less than 5.5, whereas baseline separation between VD and MF was not achieved. Separation quality is important; thus, the typical key response is good resolution between critical analyte peaks [ 56 , 57 , 58 ]. Similar work has been reported on different drugs in which the resolution was the only response, while buffer pH, percentage acetonitrile, and flow rate had a significant effect on the response [ 51 , 52 , 53 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A preliminary study showed that using more than 70% acetonitrile in the mobile phase eluted MF after 7 min at a pH less than 5.5, whereas baseline separation between VD and MF was not achieved. Separation quality is important; thus, the typical key response is good resolution between critical analyte peaks [ 56 , 57 , 58 ]. Similar work has been reported on different drugs in which the resolution was the only response, while buffer pH, percentage acetonitrile, and flow rate had a significant effect on the response [ 51 , 52 , 53 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The first-order influence of all three parameters showed a substantial effect on the separation between VD and MF ( p < 0.05), whereas the effect of all three parameters on the resolution between RE and VD was not significant, as confirmed by the p -values < 0.001 and >0.05, respectively. For the prediction of a response, a significant model is required [ 57 ]. A significant model with p < 0.05 indicates that one or more variable parameters have a significant influence on the mean response [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are similar advantages of applying QbD principles to analytical methods as to manufacturing processes and product [9]. Several researchers have implemented QbD principles to analytical methods development process [10][11][12][13][14][15]. AQbD approach can be used in the development of a robust and cost-effective analytical method which is applicable at any stage of the lifecycle of the product.…”
Section: Introductionmentioning
confidence: 99%
“…The final step is continual improvement which can be done in the form of adjustments of the working point inside the validated MODR. A number of case studies following this approach can be found in the literature [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%